Software Package for Identification and Processing of Multidimensional Time Series by Spline Functions (Eurasian Journal of Engineering and Technology, 2022)
Constructive approaches, principles, new methods are proposed to ensure timely and efficient transformation and processing of large volumes of non-stationary time series based on the use of neural networks. Algorithms and software tools for restoring time series and training neural networks for modeling by methods of spline functions have been developed and implemented.